2022
DOI: 10.1111/1759-7714.14381
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel circ_0001946/miR‐1290/SOX6 ceRNA network in esophageal squamous cell cancer

Abstract: Background Circular RNAs (circRNAs) can function as competing endogenous RNAs (ceRNAs) to impact the development of esophageal squamous cell cancer (ESCC). Human circ_0001946 has been identified as a potential anticancer factor in ESCC, yet our understanding of its molecular basis remains limited. Methods Circ_0001946, microRNA (miR)‐1290 and SRY‐box transcription factor 6 (SOX6) were quantified by quantitative reasl‐time PCR (qRT‐PCR) or immunoblotting. Cell proliferation was assessed by CCK‐8 and EDU assays.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…Yao et al [ 13 ] reported that circ_0001946 was significantly upregulated in LUAD tumor tissues, but Zhang et al [ 22 ] found that the median expression level of circ_0001946 in NSCLC tissues was more than 3 times higher than that in tumor tissues. Besides, the expression of circ_0001946 in tumor tissues was also significantly lower than in tumor tissues in esophageal adenocarcinoma (ESCC) [ 23 ]. All in all, it is inconclusive whether circ_0001946 plays an anticancer or inhibitory role in malignant tumors since its expression may be affected by various factors.…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al [ 13 ] reported that circ_0001946 was significantly upregulated in LUAD tumor tissues, but Zhang et al [ 22 ] found that the median expression level of circ_0001946 in NSCLC tissues was more than 3 times higher than that in tumor tissues. Besides, the expression of circ_0001946 in tumor tissues was also significantly lower than in tumor tissues in esophageal adenocarcinoma (ESCC) [ 23 ]. All in all, it is inconclusive whether circ_0001946 plays an anticancer or inhibitory role in malignant tumors since its expression may be affected by various factors.…”
Section: Discussionmentioning
confidence: 99%
“… MicroRNAs targeting the pathways of Wnt/β-catenin, IL6/Stat3, and TGF-β in esophageal squamous cell carcinoma metastasis. In esophageal squamous cell carcinoma (ESCC), miRNAs serve as crucial effector to Wnt/β-catenin, IL-6/STAT3 and TGF-β signalings, which is consistently involved in cancer metastasis[ 9 , 12 , 14 , 23 , 27 , 28 , 33 , 44 , 59 , 61 , 70 , 73 , 78 , 80 , 81 , 83 , 85 , 86 , 88 - 91 , 93 - 95 , 109 , 111 , 113 , 114 , 116 , 118 , 119 , 142 - 144 , 151 , 156 , 161 , 164 , 165 , 169 , 174 , 178 , 181 , 189 , 193 , 195 , 200 , 201 , 204 , 209 , 211 , 215 , 219 , 227 , 229 , 235 , 238 , 253 , 263 , 270 , 273 , 284 - 287 , 289 , …”
Section: The Genetic Mechanism Of Mirnas On Escc Metastasismentioning
confidence: 99%
“…For example, both of miR-1269 and miR-1290 act as oncomiRs, and are upregulated in ESCC tissues and cell lines. They are associated with positive LNM and/or advanced TNM stage, and their overexpression promotes the malignant transformation of ESCC cells, including migration and invasion, by directly targeting SRY-box transcription factor 6, interactive with β-catenin (SOX6)[ 59 , 113 ]. Furthermore, the downregulation of miR-4429 has been shown to foster ESCC cell invasion and migration by partially regulating β-catenin through the direct targeting of SRXN1[ 114 ].…”
Section: The Genetic Mechanism Of Mirnas On Escc Metastasismentioning
confidence: 99%
See 1 more Smart Citation